Proceedings Of The Meeting Of The Board Of Directors, April 28, 1916 (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1916)
The following delegates were appointed to the National Conservation Congress on May 2, 3, and 4, 1916, in Washington, D. C. HENRY S.. DRINKER, a GEORGE OTIS SMITH, A. F. Lucas, - W. L. SAUNDERS, VAN H. MANNING. President Ricketts was appointed delegate to the dedication ceremonies of the new buildings of the Massachusetts Institute of Technology in June. W. L. Saunders was appointed delegate to the ceremonies in celebration of the 150th Anniversary of the founding of Rutgers College to be held in October. George C. Stone was appointed delegate to the meeting on Standard Screen Scale of the U. S. Bureau of Standards. George D. Barron and Thomas T. Read were appointed delegates to the Second National Exposition of Chemical Industries to be held in New York in September. It was resolved, that the Institute shall pay the transportation of the Secretaries of the Local Sections to and from the Arizona Meeting. It was resolved that certain general topics' should be selected for discussion at the next meeting of the Institute and a session devoted to each.